DINAMIKA KEPEMIMPINAN POLITIK DALAM MEWUJUDKAN STABILITAS NEGARA - Zulhidayat, M. Reyza; Suharni Haris; Oksahil; Restiawati; Ahmad Dahlan Al Haris (UNIVERSITAS SERAMBI MEKKAH, 2024)
The movement power of a country to become more advanced or perhaps to become more backward is largely determined by how the leader influences the movement of that country, through the relationship between the leader himself and the people in a country, in carrying out his duties and responsibilities to realize the stability of the country. The ability to influence is determined by the leadership style applied by the leader to the circumstances or situations faced within the country, meaning that the leader can adapt his leadership style to the movement for change. Leadership style can increase the country's movement power to become dynamic following the progress that a country wants to achieve. Not afraid of change, even the changes are planned so that the country is able to compete with global changes. These leadership styles show variations in leadership or leadership dynamics that can bring about state stability. The research method is qualitative with observational data collection techniques.